Students’ perspectives on bilingualism in Indonesian EFL classroom: A case study on teachers' L1 use as one of EMI - Noviyati, Dewi; Suwandi, Suwandi; Senowarsito, Senowarsito (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
In today’s interconnected world, where global communication is more accessible than ever, English has emerged as the dominant lingua franca. As a result, bilingual and multilingual speakers of English are increasingly common. Within the Indonesian EFL (English as a Foreign Language) context, bilingualism—often extending to multilingualism—has become a prevalent phenomenon, particularly due to the predominance of non-native English-speaking teachers who share the same first language (L1) as their students. This situation has led to the proposal of a "multilingual model" for English teaching, advocating for the strategic use of L1 and its associated culture to support second language (L2) acquisition. In contrast, the traditional "native speaker model" has been widely critiqued. Despite these proposals, the role of L1 in the EFL classroom remains contentious, particularly in Indonesia, where critics argue that its use reflects teachers' inadequacies in English proficiency. This study explores the use of L1 in the EFL classroom from the perspective of students, as they are directly affected by the linguistic practices employed. By focusing on students' perceptions, this paper provides valuable insights for educators, scholars, and policymakers regarding the implications of L1 use in facilitating or hindering English language learning in the classroom.